Huisheng Oral Solution Adjunct With Platinum-Based Chemotherapy for the Treatment of Advanced Non-Small Cell Lung Cancer: A Meta-Analysis and Systematic Review - Jingyi Huang; Zhichao Wang; Han Xue; Ailing Cao; Ailing Cao; Cassidy Turner; Jing Wang; Li Zhang; Jinghai Wang; Na Xiao; Na Xiao; Jie Xu; et al. (Frontiers Media S.A., 2020)
BackgroundPlatinum-based chemotherapy is one of the first line therapies for the advanced non-small cell lung cancer (NSCLC), even though its high toxicity and limited clinical effects cannot be neglected. Huisheng oral solution (HSOS) has been widely used as an adjuvant chemotherapy drug for NSCLC in China. To systematically analyze the therapeutic effects of the combination of HSOS and platinum-based chemotherapy, a comprehensive meta-analysis was performed.ObjectivesThis systematic review and meta-analysis aimed to evaluate the effectiveness and safety of HSOS for NSCLC.MethodsThe randomized controlled trials (RCTs) were selected on seven medical databases up to June 2020, including advanced NSCLC treatment using HSOS plus platinum-based chemotherapy versus chemotherapy alone. We followed the PRISMA checklist in general, applying Cochrane handbook 5.1.0, GRADE Pro GDT, RevMan 5.3, Stata12.0, and TSA 0.9.5.10 Beta to evaluate the quality of the study and analyze the data.ResultsBased on Cochrane handbook 5.1.0, 15 RCTs consisting 1165 patients met the criteria and were selected for further analysis. Compared to chemotherapy alone, the chemotherapy combined with HSOS significantly improved objective tumor response (ORR) [RR = 1.38, 95% CI (1.19, 1.59), P < 0.0001], disease control rate (DCR) [RR = 1.10, 95% CI (1.04, 1.16), P = 0.0006], and Karnofsky performance status (KPS) [RR = 1.79, 95% CI (1.41, 2.26), P < 0.00001]. However, there was no evidence of improvement in the 1-year survival rate [RR = 1.37, 95% CI (0.98, 1.92), P = 0.07]. In terms of the side effects, HSOS administered concurrently with chemotherapy resulted in a serial of substantial benefits: lower toxicity to white blood cell [RR = 0.30, 95% CI (0.20, 0.43), P < 0.00001], lower platelet toxicity [RR = 0.56, 95% CI (0.34, 0.92), P = 0.02], and reduced incidence of vomiting [RR = 0.52, 95% CI (0.29, 0.92), P = 0.03].ConclusionsThe meta-analysis indicated that HSOS plus platinum-based chemotherapy was more beneficial for patients, as the therapy could synergize antitumor activity and could attenuate toxicity. The finding requires confirmation by further rigorously designed RCTs.